Prognostic value of the PDW/HDL-C ratio in patients with chest pain symptoms and coronary artery calcification - Qiu, Ya-Jing; Luo, Jun-Yi; Luo, Fan; Tian, Xin-Xin; Zeng, Lu; Zhang, Zhuo-Ran; Li, Xiao-Mei; Yang, Yi-Ning (Frontiers in Cardiovascular Medicine, 2022)
Background Platelet-related parameters and HDL-C have been regarded as reliable and alternative markers of coronary heart disease (CHD) and the independent predictors of cardiovascular outcomes. PDW is a simple platelet index, which increases during platelet activation. Whether the PDW/HDL-C ratio predicts major adverse cardiovascular and cerebrovascular events (MACCEs) in patients who complained of chest pain and confirmed coronary artery calcification remains to be investigated. This study aimed to investigate the prognostic value of the PDW/HDL-C ratio in patients with chest pain symptoms and coronary artery calcification. Methods A total of 5,647 patients with chest pain who underwent coronary computer tomography angiography (CTA) were enrolled in this study. Patients were divided into two groups according to their PDW/HDL-C ratio or whether the MACCE occurs. The primary outcomes were new-onset MACCEs, defined as the composite of all-cause death, non-fatal MI, non-fatal stroke, revascularization, malignant arrhythmia, and severe heart failure. Results All patients had varying degrees of coronary calcification, with a mean CACS of 97.60 (22.60, 942.75), and the level of CACS in the MACCEs group was significantly higher than that in non-MACCE (P<0.001). During the 89-month follow-up, 304 (5.38%) MACCEs were recorded. The incidence of MACCEs was significantly higher in patients with the PDW/HDL-C ratio > 13.33. The K–M survival curves showed that patients in the high PDW/HDL-C ratio group had significantly lower survival rates than patients in the low PDW/HDL-C ratio group (log-rank test: P < 0.001). Multivariate Cox hazard regression analysis reveals that the PDW/HDL ratio was an independent predictor of MACCEs (HR: 1.604, 95% CI: 1.263–2.035; P < 0.001). Cox regression analysis showed that participants with a lower PDW/HDL-C ratio had a higher risk of MACCEs than those in the higher ratio group. The incidence of MACCEs was also more common in the PDW/HDL-C ratio > 13.33 group among different severities of coronary artery calcification. Furthermore, adding the PDW/HDL-C ratio to the traditional prognostic model for MACCEs improved C-statistic (P < 0.001), the NRI value (11.3% improvement, 95% CI: 0.018–0.196, P = 0.01), and the IDI value (0.7% improvement, 95% CI: 0.003–0.010, P < 0.001). Conclusion The higher PDW/HDL-C ratio was independently associated with the increasing risk of MACCEs in patients with chest pain symptoms and coronary artery calcification. In patients with moderate calcification, mild coronary artery stenosis, and CAD verified by CTA, the incidence of MACCEs increased significantly in the PDW/HDL-C ratio > 13.33 group. Adding the PDW/HDL-C ratio to the traditional model provided had an incremental prognostic value for MACCEs.